Efeito do congelamento e estocagem sobre a qualidade da carne bovina - Michelle Moreira Machado (2009)
The effect of freezing and storage of beef (m. Longissimus dorsi) at -18 °C was evaluated at six pairs of m. Longissimus dorsi (twelve samples) from six castrated male cattle, with estimated age of two years identified as intermediaries age, and all samples with a pH final in the range of 5.4 to 5.9. The samples were prepared in different forms (ground, steak and whole) and kept for 30, 60 and 120 days under storage at -18 °C, result a total of 144 sub-samples. It was determined the proximate composition, pH, water holding capacity (WHC), loss of weight, shear force(WBSF) and quantification of lipid oxidation. There were no significant effect of time of storage or the forms on pH, proximate composition, loss of juices, and WBSF. The ground beef had higher (P <0.05) value of WHC, and time of storage has no effect on this parameter. The values of loss evaporation, during cooking, and lipid oxidation increased with time of storage, with higher cooking losses observed for the entire form and higher lipid oxidation for ground beef